A post-occupancy evaluation on indoor environment and its significance on learning performance / Pangiran Shafiq Pangiran Julaini, Yuhainis Abdul Talib and Husrul Nizam Hussin - Pangiran Julaini, Pangiran Shafiq; Abdul Talib, Yuhainis; Hussin, Husrul Nizam (2022)
Malaysia's tropical climate is hot and humid. This situation could have an adverse impact on occupant comfort in any place. It is reported that in 2018, all schools in Kedah and Perlis were closed for two days due to extremely hot and dry weather caused by El Nino Phenomenon. In Malaysia, a study found that the occupant was not satisfied with the number of occupants inside the building which was too crowded. The objectives of this research are to identify occupant satisfaction towards an indoor environment in the classroom and to analyze the relationship between the indoor environment and their learning performance. A field experiment using sets of questionnaires was conducted at three colleges in Perlis to study the objectives. Descriptive analysis was used to analyze the data. The result found that the occupant satisfaction towards the indoor environment in the classroom is at the average level while the relationship between indoor environment and learning performance is at the average level. The multiple regression analysis conducted shows that four factors (temperature, lighting, design or space, and ventilation) and learning performance correlatively influence the occupant satisfaction towards the indoor environment in the classroom.